The Full Day School System and School Environment on the Formation of Student Character at MAN 8 Jombang - Ira Nur Agustin; Heru Totok Tri Wahono (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Student character formation is one of the central objectives of education, and the implementation of a full-day school system and a supportive school environment is considered important in strengthening students’ character development. However, challenges remain, including student fatigue caused by extended learning hours and variations in the internalization of character values among students. This study aimed to analyze the effect of the full-day school system, the school environment, and their simultaneous influence on student character formation at MAN 8 Jombang. A quantitative approach with a survey method was employed. The population consisted of 753 students, from which 262 students were selected using proportional random sampling. Data were collected through observation, documentation, and direct questionnaire distribution, and were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The findings indicate that the full-day school system has a positive effect on student character formation, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.318. The school environment also has a positive effect, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.412. Simultaneously, both variables significantly influence student character formation, as indicated by an F-value of 188.615 and a coefficient of determination (R²) of 0.593. This means that the full-day school system and school environment collectively contribute 59.3% to student character formation, while the remaining 40.7% is explained by other factors outside the scope of this study. The study concludes that improving the quality of full-day school implementation and strengthening school environmental management are essential for sustainable character formation. These findings provide practical implications for schools, teachers, students, and parents to build collaborative character education practices in madrasah contexts.